DAMPAK MINIMARKET (ALFAMART DAN INDOMARET) TERHADAP TINGKAT PENGELUARAN DAN POLA KONSUMSI MASYARAKAT DI KECAMATAN KERTAK HANYAR - SAPTIAN HADI (PPJP Universitas Lambung Mangkurat, 2018)
This research is conducted to know: (1) minimarket impact to society expenditure level in Kecamatan Kertak Hanyar. (2) change of society consumption pattern after minimarket.The analysis method used is paired t-test. The research variable is the level of public expenditure before and after there minimarket in Kecamatan Kertak Hanyar. The data source is the primary data obtained through direct interviews to the people who shop in the minimarket using questionnaires.The results of the calculation using paired t-test showed a decrease in expenditure level of the shopping community in the traditional market after the minimarket and the shift of consumption patterns from the traditional market to the minimarket.